2019
DOI: 10.1002/bab.1843
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of possible pattern‐recognition receptors to advanced glycation end product–induced cellular responses in macrophage‐like RAW264.7 cells

Abstract: Advanced glycation end products (AGEs) are considered to be related to the pathogenesis of some inflammatory diseases. AGEs were reported to stimulate the receptor for AGEs (RAGE), which causes inflammatory reactions. However, recently, toll‐like receptors (TLRs), in addition to RAGE, have been reported to be related to AGE‐mediated cellular responses, and it remains unclear which receptor is responsible for AGE recognition. To reveal the role of pattern‐recognition receptors, including TLRs and/or RAGE, in AG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…RAGE‐deficient RAW 264.7 cells revealed that the contribution of RAGE to AGE ( ie , glyceraldehyde‐modified BSA)‐dependent TNF‐α expression was slight, but significantly decreased compared to RAGE‐sufficient control cells 82 . Recognition of AGE in this model was more dependent on TLR2 and TLR4 82 .…”
Section: Rage and Tlr4 Crosstalkmentioning
confidence: 77%
See 2 more Smart Citations
“…RAGE‐deficient RAW 264.7 cells revealed that the contribution of RAGE to AGE ( ie , glyceraldehyde‐modified BSA)‐dependent TNF‐α expression was slight, but significantly decreased compared to RAGE‐sufficient control cells 82 . Recognition of AGE in this model was more dependent on TLR2 and TLR4 82 .…”
Section: Rage and Tlr4 Crosstalkmentioning
confidence: 77%
“…RAGE‐deficient RAW 264.7 cells revealed that the contribution of RAGE to AGE ( ie , glyceraldehyde‐modified BSA)‐dependent TNF‐α expression was slight, but significantly decreased compared to RAGE‐sufficient control cells 82 . Recognition of AGE in this model was more dependent on TLR2 and TLR4 82 . Since it is well established that LPS pretreatment of cells induces a transient state of LPS‐hyporesponsiveness (“tolerance”) upon restimulation (reviewed by 83 ), this partial recognition of AGE by TLR4 may explain how LPS pretreatment can tolerize human monocytes to a second stimulation with AGEs 84 .…”
Section: Rage and Tlr4 Crosstalkmentioning
confidence: 97%
See 1 more Smart Citation
“…Also called AGER, its name obviously derives from its ability to bind AGEs. Therefore, in addition to exert direct effects brought about by RCS reactions, carbonyl stress can induce indirect biological effects through binding of AGEs to receptors of the innate immune system and induction of a chronic inflammatory response [104]. In particular, AGE binding to RAGE activates transcription factors and redox sensitive signaling pathways leading to reactive oxygen species formation, inflammation, fibrosis, autophagy, proliferation, etc.…”
Section: Diabetes Carbonyl Stress Advanced Glycation End-products (Ages) Formation and Related Therapeutic Strategiesmentioning
confidence: 99%
“…Recent work has demonstrated that ALEs on albumin that involve neutralization of a positive charge surrounded by acidic residues are also binders of RAGE ( 75), unveiling a novel mechanism for influencing immune function. AGEs and ALEs are essentially damage-associated molecular patterns (DAMPs); AGEs can also interact with other pattern recognition receptors, such as Toll-like receptors (76), and ALEs are considered to be oxidation-specific epitopes with effects on innate immunity (77).…”
Section: Cellular Outcomes Of Lipoxidationmentioning
confidence: 99%